2012
DOI: 10.1016/j.gmod.2012.05.006
|View full text |Cite
|
Sign up to set email alerts
|

H2 regularity properties of singular parameterizations in isogeometric analysis

Abstract: Graphical abstractHighlights► We consider the isogeometric method for singularly parameterized domains. ► In this case the underlying function space may not be sufficiently regular. ► We especially focus on H2 regularity for 1-, 2- and 3-dimensional domains. ► We introduce a modification scheme for the test function space to regain regularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Then, if we look at 'Case I' from in Sec. 4. of [23], we get with Theorem 4.4. from latter article that the coupled SB-IGA test functions are in H 2 (Ω m ) for each patch. To see this, we observe that we use for the coupling method only such B-splines B r i,p • B r j,p with j > 2 or the additional scaling center test functions, which are obviously smooth in a whole neighborhood of the scaling center.…”
Section: Remarks On Stabilitymentioning
confidence: 83%
“…Then, if we look at 'Case I' from in Sec. 4. of [23], we get with Theorem 4.4. from latter article that the coupled SB-IGA test functions are in H 2 (Ω m ) for each patch. To see this, we observe that we use for the coupling method only such B-splines B r i,p • B r j,p with j > 2 or the additional scaling center test functions, which are obviously smooth in a whole neighborhood of the scaling center.…”
Section: Remarks On Stabilitymentioning
confidence: 83%
“…Singularly-parameterized C 1 surface constructions include [2, 3, 4, 5, 6, 7, 10]; [9] even shows how to construct C 2 surfaces (but specifies no rules that generically yield good shape). Independently, in the context of iso-geometry, Takacs and Jüttler [11] discussed singular spline constructions for analysis and observed that specific linear combinations of singular splines can be sufficiently regular for iso-geometric analysis. The monograph [12] characterizes subdivision surfaces as smooth spline surfaces with singularities at the irregular points and establishes the differential-geometric properties of subdivision surfaces at the singularities.…”
Section: Introductionmentioning
confidence: 99%
“…A major contribution of Reif’s singular construction [Rei97] was a proof showing that the corner singularity is removable by a local change of variables; and that the resulting surface is tangent continuous at and near the central irregular point where more of fewer than four tensor-product patches come together. More recently, in the context of iso-geometry, Takacs and Jüttler [TJ12] analyzed singular spline constructions, but did not draw the connection to the earlier surface constructions. They observed that specific linear combinations of singular splines can be sufficiently regular for isogeometric analysis and closed with the prediction that “main targets for further analysis are approximation properties on singular domains”.…”
Section: Introductionmentioning
confidence: 99%